2023
DOI: 10.1038/s41598-023-43803-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical species and temperature on the stability of air nanobubbles

Seyed Mohammad Montazeri,
Nicolas Kalogerakis,
Georgios Kolliopoulos

Abstract: The colloidal stability of air nanobubbles (NBs) was studied at different temperatures (0–30 °C) and in the presence of sulfates, typically found in mining effluents, in a wide range of Na2SO4 concentrations (0.001 to 1 M), along with the effect of surfactants (sodium dodecyl sulfate), chloride salts (NaCl), and acid/base reagents at a pH range from 4 to 9. Using a nanobubble generator based on hydrodynamic cavitation, 1.2 × 108 bubbles/mL with a typical radius of 84.66 ± 7.88 nm were generated in deionized wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…Indeed, this is corroborated by previous studies showing that NBs are much less stable under acidic conditions than in neutral to basic solutions. 25,59,63 In our proposed model, the solvent and any ions or additives that may be present induce a dipole on the NB surface by dipole-induced dipole or ion-induced dipole interactions. We also know from the theory of colloidal stability developed by Derjaguin, Landau, Verwey, and Overbeek (DLVO) that the magnitude of the induced surface charge or the zeta potential directly controls the colloidal stability of monodisperse systems.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, this is corroborated by previous studies showing that NBs are much less stable under acidic conditions than in neutral to basic solutions. 25,59,63 In our proposed model, the solvent and any ions or additives that may be present induce a dipole on the NB surface by dipole-induced dipole or ion-induced dipole interactions. We also know from the theory of colloidal stability developed by Derjaguin, Landau, Verwey, and Overbeek (DLVO) that the magnitude of the induced surface charge or the zeta potential directly controls the colloidal stability of monodisperse systems.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Bulk nanobubbles (NBs) are a class of materials that consist of bubbles with dimensions on the nanometer scale that have captured the interest of scientists and engineers from a variety of disciplines. These materials have found application in an assortment of areas, such as water treatment and disinfection, agriculture and hydroponics, and most recently, advanced chemical oxidation processes. Unlike bubbles of larger diameter (>1 μm), NBs are known to be stable in water for long periods of time. The standard model currently adopted in the literature to explain this stability involves a balance between the Laplace pressure and the pressure from electrostatic interactions at the NB-solvent interface. In general, we can express this balance using the Young–Laplace equation as follows: P 0 + P YL = P NB + P e where P 0 is the pressure of the atmosphere outside the solution, P YL is the Laplace pressure, P NB is the pressure inside the NB, and P e is the electrostatic pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using micro-imaging technology, Wang et al 9 studied the effect of floc size on the separation efficiency in a flotation cell and indicated that small flocs are more favorable for the high separation efficiency. It was found that the existence of efficient bubble-particle contact is initially controlled by DAF hydrodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In the research study conducted by Montazeri et al 9 , the impact of adding chemicals on ultrafine nanobubbles stability was examined, but the contact between oil droplets and bubbles in the presence of chemical materials wasn’t determined. They have found that in alkaline solutions, ultrafine bubbles are more stable compared to the bubbles in acidic solutions.…”
Section: Introductionmentioning
confidence: 99%